2020
DOI: 10.1016/j.diabres.2020.108331
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical features of critically ill patients with COVID-19 in Greece: The burden of diabetes and obesity

Abstract: Highlights Critically ill Covid-19 patients with type-2 diabetes show decreased survival rate. Obese critically ill Covid-19 pneumonia patients are more often of younger age. Non-obese Covid-19 pneumonia survivors are older than obese survivors. Age and cardiovascular disease in Covid-19 patients are not related to early death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 24 publications
4
66
1
1
Order By: Relevance
“…From this meta-analysis, it was found that obese patients with COVID-19 had a higher risk to die compared to non-obese patients. Consistent results were found from several studies [ 14 , 70 , 72 ]. The history of smoking among COVID-19 patients increased the risk of mortality.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…From this meta-analysis, it was found that obese patients with COVID-19 had a higher risk to die compared to non-obese patients. Consistent results were found from several studies [ 14 , 70 , 72 ]. The history of smoking among COVID-19 patients increased the risk of mortality.…”
Section: Discussionsupporting
confidence: 92%
“…Among the included studies, 26 studies were conducted in China [ 10 13 , 26 – 47 ], 8 in USA [ 48 – 55 ], 7 in Italy [ 16 , 56 – 61 ], 4 in Spain [ 14 , 62 – 64 ], 2 in South Korea [ 65 , 66 ], 2 in Mexico [ 67 , 68 ], 1 in Bangladesh [ 69 ], 1 in Brazil [ 70 ], 1 in England [ 71 ], I in Greece [ 72 ], 1 in Iran [ 73 ], 1 in Kuwait [ 74 ], 1 in Switzerland [ 75 ], 1 in Turkey [ 76 ] and 1 in few European countries [ 77 ]. The sample size of the included studies varied from 16 to 51,633 patients and the mean age of the included patients varied from 41 years to 85.5 years.…”
Section: Resultsmentioning
confidence: 99%
“…In the group of COVID-19 mortality, the average prevalence of cardio-cerebrovascular disease was 15.15%. Seventeen studies ( Buckner et al, 2020 ; Cao et al, 2020 ; Guan et al, 2020 ; Huang et al, 2020 ; Khamis et al, 2020 ; Y. Li et al, 2020 ; Mao et al, 2020 ; Mendy et al, 2020 ; Petrilli et al, 2020 ; Romero-Sanchez et al, 2020 ; Wang et al, 2020 ; Wei et al, 2020 ; Xie et al, 2020 ; Xu et al, 2020 ; S. Yan et al, 2020 ; G. Zhang et al, 2020 ; J. J. Zhang et al, 2020 ) reported the disease severity of COVID-19 patients with cardio-cerebrovascular disease, and 14 studies ( T. Chen et al, 2020 ; Du et al, 2020 ; Halvatsiotis et al, 2020 ; Inciardi et al, 2020 ; Mehra et al, 2020 ; Nikpouraghdam et al, 2020 ; Ruan et al, 2020 ; Soares et al, 2020 ; Sousa et al, 2020 ; Tu et al, 2020 ; Wu et al, 2020 ; Y. Yan et al, 2020 ; Yuan et al, 2020 ; Zhou et al, 2020 ) reported the mortality of COVID-19 patients with cardio-cerebrovascular disease.…”
Section: Resultsmentioning
confidence: 99%
“…Another Mexican study with 51,633 patients showed similar results, with a significant increased lethality rate in patients with obesity (HR: 1.25 (1.17–1.34, p < 0.001) [ 27 ]. These reports with large patient cohorts are further strengthened by multiple clinical studies with smaller collectives worldwide [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Interestingly, Lighter et al and Ebinger et al showed that middle aged patients with an age below 52 and up to 60 years were more affected by obesity (BMI 30–34 and ≥35) with an HR: 2.0 (1.6–2.6, p < 0.0001)) and HR: 2.2 (1.7–2.9, p < 0.0001), respectively, resulting in increased morbidity rates compared to >60 years old patients [ 31 , 43 ].…”
Section: Clinical Correlation Of Covid-19 With Obesitymentioning
confidence: 92%